LAW ENFORCEMENT OF THE CRIME OF MONEY LAUNDERING THAT COMES FROM ONLINE GAMBLING - Murshal Senjaya (International Journal of Social Science, 2022)
Law enforcement by the police in the crime of money laundering originating from online gambling is associated withLaw Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering is an online gambling law enforcement that has been carried out by the VC Sat Subunit. The Criminal Police Criminal Investigation Unit still uses the instrument of Article 303 of the Criminal Code rather than Article 27 paragraph (2) Jo. Article 45 of the ITE Law. The threat of imprisonment under Article 303 of the Criminal Code is 10 years, heavier than Article 27 (2) Jo. Article 45 of the ITE Law which is only 6 years old.Obstacles and law enforcement efforts by the police in the crime of money laundering originating from online gambling are associated withLaw Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering isThe human resource factor in an effort to eradicate online gambling crime is one of the important factors. Lack of mastery and understanding of personnel in the information technology sector. The external inhibiting factor in eradicating online gambling crimes is the server factor placed in countries that legalize gambling, the factor of using a Virtual Private Network (VPN).